1995
DOI: 10.1111/j.1399-6576.1995.tb04034.x
|View full text |Cite
|
Sign up to set email alerts
|

Plasma cholinesterase and abnormal reaction to succinylcholine: twenty years' experience with the Danish Cholinesterase Research Unit

Abstract: For more than 20 years, the Danish Cholinesterase Research Unit (DCRU) has collected information about patients showing an abnormal response to succinylcholine. The purpose of this study was, on the basis of the 20 years' experiences with the Unit, to evaluate our clinical findings in patients referred because of prolonged response following succinylcholine. Also, we wanted to evaluate the results of our prospective controlled studies of the effect of succinylcholine in patients with normal and abnormal plasma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
3

Year Published

2003
2003
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(25 citation statements)
references
References 27 publications
0
22
0
3
Order By: Relevance
“…In one series of 1247 patients, inhibition studies revealed a genetic cause in 47% of patients, whereas low activity of the usual enzyme due to other factors such as pregnancy was identified in ϳ7% of patients. Most of the remaining patients (39%) did not have a clearly identifiable cause, largely because of equivocal "genotyping" (inhibition studies) (Jensen and Viby-Mogensen, 1995). In another study, 52 (80%) of 65 patients with a history of suxamethonium apnea had reduced BChE activity caused by variations in the BCHE gene (Yen et al, 2003).…”
Section: B Butyrylcholinesterasementioning
confidence: 99%
“…In one series of 1247 patients, inhibition studies revealed a genetic cause in 47% of patients, whereas low activity of the usual enzyme due to other factors such as pregnancy was identified in ϳ7% of patients. Most of the remaining patients (39%) did not have a clearly identifiable cause, largely because of equivocal "genotyping" (inhibition studies) (Jensen and Viby-Mogensen, 1995). In another study, 52 (80%) of 65 patients with a history of suxamethonium apnea had reduced BChE activity caused by variations in the BCHE gene (Yen et al, 2003).…”
Section: B Butyrylcholinesterasementioning
confidence: 99%
“…In such patients there is a wide variability in the neuromuscular blocking effect, onset and duration of paralysis caused by succinylcholine (16,17). The mechanisms by which normal and eclamptic pregnancies cause a reduction in plasma cholinesterase activity are not fully known.…”
Section: Discussionmentioning
confidence: 99%
“…17,18 Human BChE has been sequenced, and has been shown to contain four identical subunits (tetramer); each subunit contains 574 amino acids, and the tetramer has a total weight of 342,000 Da. 19 BChE is synthesized in the liver.…”
Section: Dovepressmentioning
confidence: 99%